Opportunities and Challenges in the Development of Cathode Materials for Rechargeable Mg Batteries - Bitenc, Jan; Dominko, Robert (Frontiers in Chemistry, 2018)
Recent years have seen an intense and renewed interest in Mg battery research, naming Mg-S the »Holy Grail« battery, and expectations that Mg battery system will be able to compete and surpass Li-ion batteries in a matter of years. While considerable progress has been achieved in the field of Mg electrolytes, where several new electrolytes with improved electrochemical performance and favorable chemical properties (non-corrosive, non-nucleophilic) were synthesized. Development in the field of cathodes remains a bit more elusive, with inorganic, sulfur and organic cathodes all showing their upsides and downsides. This review highlights the recent progress in the field of Mg battery cathodes, paying a special attention to the performance and comparison of the different types of the cathodes. It also aims to define advantages and key challenges in the development of each type of cathodes and finally specific questions that should be addressed in the future research.